INVESTIGATING THE INFLUENCE OF SMART GRID TECHNOLOGIES ON ENERGY DISTRIBUTION AND CONSUMPTION EFFICIENCY - Dahyawan, Dodi (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background:The global demand for energy is increasing at an unprecedented rate, necessitating more efficient methods of energy distribution and consumption. Traditional energy grids are becoming less efficient in handling the dynamic needs of modern consumers, leading to significant losses and inefficiencies. Smart grid technologies, which incorporate advanced information and communication technologies, offer promising solutions to address these challenges. Aims:This study aims to investigate the influence of smart grid technologies on energy distribution and consumption efficiency. It focuses on the impact of these technologies on reducing energy losses, improving demand response, and optimizing energy consumption patterns. Research Method:A mixed-method approach is employed in this research, combining qualitative case studies and quantitative data analysis. The study examines smart grid implementations in various regions, evaluating their effects on energy distribution efficiency through statistical analysis and real-world case studies. Data was collected from energy providers, consumers, and industry experts to assess the performance of smart grid systems. Results and Conclusion:The results indicate that smart grid technologies significantly improve the efficiency of energy distribution and consumption. Key benefits include a reduction in energy losses, better integration of renewable energy sources, enhanced demand response capabilities, and overall cost savings. However, challenges such as high initial investment costs and technological integration hurdles remain. The conclusion emphasizes the need for continued innovation and policy support to fully realize the potential of smart grids in achieving sustainable energy systems. Contribution:This study contributes to the understanding of how smart grid technologies can transform energy systems by enhancing efficiency and sustainability. It provides valuable insights for policymakers, energy providers, and researchers looking to adopt or improve smart grid technologies.